Mapping Emerging Themes in Business Relationship Capability Studies: A VOSviewer-Based Bibliometric Analysis - La Ode Sugianto; Titis Purwaningrum; Siti Chamidah; Dwi Warni Wahyuningsih; Wa Ode Sitti Nurrahmah (Global Research and Collaboration, 2026)
This study employed a quantitative bibliometric approach using 469 open-access Scopus-indexed publications. Data were analyzed using VOSviewer through keyword co-occurrence, network visualization, overlay visualization, density visualization, and co-authorship analyses to examine conceptual relationships, thematic evolution, and international scientific collaboration. The findings reveal a substantial increase in BRC publications, particularly between 2024 and 2025, reflecting growing scholarly attention to relational capabilities in the digital economy. Network visualization identifies digital transformation, dynamic capability, organizational resilience, digital capability, and business model innovation as the dominant conceptual foundations of BRC. Overlay visualization highlights emerging themes, including AI capability, digital ecosystems, sustainability, and the circular economy, while density visualization confirms that transformation, resilience, and business model innovation constitute the core knowledge structure of the field. Co-authorship analysis further demonstrates strong international collaboration led by China, the United States, the United Kingdom, India, and Indonesia, indicating the global and multidisciplinary nature of BRC research. This study extends the application of bibliometric mapping to the BRC domain by providing a comprehensive understanding of its intellectual structure, thematic evolution, and global collaboration patterns. It reinforces Dynamic Capabilities Theory by positioning BRC as a strategic capability that integrates relational resources, digital transformation, organizational resilience, and business model innovation. The findings offer a valuable research agenda for future studies on AI-enabled collaboration, digital ecosystems, sustainability-oriented innovation, and organizational resilience, while providing practical insights for managers seeking to strengthen digital competitiveness through collaborative capabilities.